Comparison of macroalgae meadows in warm Atlantic versus cold Arctic regimes in the high-Arctic Svalbard - Wiktor, Józef M.; Tatarek, Agnieszka; Kruss, Aleksandra; Singh, Rakesh Kumar; Wiktor, Józef M.; Søreide, Janne E. (Frontiers in Marine Science, 2022)
A warmer Arctic with less sea ice will likely improve macroalgae growth conditions, but observational data to support this hypothesis are scarce. In this study, we combined hydroacoustic and video inspections to compare the depth of growth, density and thickness of macroalgae (>10 cm) meadows in two contrasting climate regimes in Svalbard 1) the warm, ice free, Atlantic influenced West Spitsbergen and 2) the cold, Arctic and seasonal ice covered East Spitsbergen. Both places had similar insolation and comparable turbidity levels. Macroalgae communities at both places were similar and were formed mainly by common north Atlantic kelp species: Saccharina latissima, Alaria esculenta, Laminaria digitata and L. hyperborea. However, the density of the bottom coverage and thalli condition were strikingly different between the two sites. Algae at the warmer site were intact and fully developed and occupied most of the available hard substrate. At the colder site, only patchy macroalgae canopies were found and most thallies were physically damaged and trimmed at a uniform height due to physical ice scouring. These differences in macroalgal density and thalli condition were only found at depths down to 5 m. Deeper, no distinct differences were observed between the warm and cold sites. Sea urchins were only observed at the warm site, but in few numbers with no visible negative top-down control on macroalgae growth.